Psychological situations of elite Turkish female athletes in premenstrual period - Tasgin , Ö. (Archives of Budo, 2013)
Background and Study Aim: In the last 20 years female participation in sports increased due the passage of particular act. According to this law the discrimination against female athletes in sports was relatively decreased. Aim of this study was the menstrual situations of Turkish female team athletes and individual athletes in premenstrual syndrome period. Material and Methods: After a New Scale for Premenstrual Syndrome was conducted to the sample of the study, some significant results were gained. The menstrual situations of individual female athletes who deal with wrestling, judo, and taekwondo branches were assessed. In this study team athletes were 120 females and individual athletes were 146 females in total 266 females. The survey was conducted to these athletes. Frequency distributions were noticed according to gathered data for two or more variables and chi square and independent sample t test were applied to some of the items. Significance level was set at 5%. Results: It is seen that depressive affectivity, anxiety, exhaustion, anger, pain, appetite changes and timidity which are the conditions of premenstrual syndrome differed in a significant way in team athletes than in individual athletes. There is significant difference between the branches and the effect of participation to competition to performance in menstrual period. Conclusions: The responsibility of competitive in team sports was shared by all team athletes. In individual sports, athletes must cope with psychological and physical stresses of competitive by herself. Therefore, the findings of this study suggest that individual athletes maybe confronted with the psychological stresses during match and training